KOMPETENSI DAN PEMBERIAN TUNJANGAN FUNGSIONAL SERTA PENGARUHNYA TERHADAP KINERJA PENYULUH PERTANIAN LAPANGAN KABUPATEN MUNA BARAT - Jamal Bake; Zulfiah Larisu; Akbar Wahbi (Halu Oleo University, 2023)
The research problems are: 1) Do competence and provision of functional allowances simultaneously have a significant effect on the performance of agricultural instructors?; 2) Does competency have a significant effect on the performance of agricultural instructors?; 3) Does the provision of functional allowances have a significant effect on the performance of agricultural instructors? The approach used uses quantitative methods in answering research problems, by conducting a survey of all agricultural instructors in West Muna Regency in 11 UPTs of Agricultural Extension Centers and Agricultural Service Headquarters, totaling 68 people, and a sample of 40 respondents was determined using the Slovin method in determine the number of samples. The research instrument is a questionnaire with a Likert scale with a score range of 1-5. Data analysis used a multiple regression model, with the help of SPSS version 26. The significance test used an alpha criterion of 0.05 to test the proposed hypothesis. The results of the research were concluded: 1) Competency and provision of functional allowances simultaneously had a significant effect on the performance of agricultural extension officers; 2) Competence has a significant effect on the performance of agricultural instructors; 3) providing functional allowances also has a significant effect on the performance of agricultural instructors. Both variables show a positive influence, meaning that the better the competence and satisfactory provision of functional allowances, the better the performance of agricultural instructors.